Development and quality evaluation of health-promoting functional carabeef cookies. Issue 1 (2nd January 2018) - Goswami, Meena; Sharma, B.D.; Mendiratta, S.K.; Chaudhary, U.B.; Pathak, Vikas; Tyagi, Nitin
Abstract : Purpose: The purpose of this paper is to develop and to assess quality characteristics of functional carabeef cookies. Design/methodology/approach: Carabeef cookies were prepared with incorporation of 50 percent carabeef powder in a pre-standardized formulation and then were baked at 150-160°C for 35-40 minutes. Developed functional carabeef cookies were incorporated with 50 percent carabeef powder, 10 percent orange pulp fiber as natural fiber source, 1.5 percent guar gum as fat replacer and 20 percent of sodium caseinate as sugar replacer. Cookies were analyzed for various physical properties, proximate parameters physcio-chemical properties, instrumental textural properties, color values, sensory evaluation and complete profile estimation in terms of minerals and fatty acids analysis. Findings: Functional carabeef cookies had 4.48 times higher protein, 6.13 times higher IDF, 5.47 times higher SDF and 4.47 times higher TDF as compared to normal refined wheat flour (RWF) cookies. Functional carabeef cookies had 34.58 percent lower fat, 19.95 percent less cholesterol and 12.5 percent lower energy content as compared to normal RWF cookies. Social implications: Functional carabeef cookies had comparatively higher mineral content as well as saturated and unsaturated fatty acids in a desirable ratio. Health-promoting functional carabeef cookies might be a magnificent option to overcome the problem of malnutrition, quite prevalent among lower socio-economical strata people specifically children and women. Originality/value: Health-promoting functional carabeef cookies had higher nutritional content and acceptability, and thus could be commercialized to improve socio-economic status and health of consumers.